Complete Genome Sequence of the Probiotic Strain Lactobacillus casei BD-II - Ai, Lianzhong (American Society for Microbiology, 2011)
Lactobacillus casei BD-II, a patented probiotic strain (U.S. patent 7,270,994 B2), was isolated from homemade koumiss in China and has been implemented in the industrial production as starter cultures. Here we report the complete genome sequence of BD-II, which shows high similarity with the well-studied probiotic BL23.